2020
DOI: 10.1038/s41598-020-71014-w
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics approach revealed robust changes in amino acid and biogenic amine signatures in patients with schizophrenia in the early course of the disease

Abstract: p = 4e−04) at baseline than CSs (full details of the data generation and fitting procedures are given in Supplementary material Tables S4-S6).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 58 publications
(73 reference statements)
4
37
0
Order By: Relevance
“…We further performed a gene enrichment analysis using 227 DEGs compiled from microarray studies. Enrichment of arginine, proline metabolism pathway in our analysis is in agreement with the findings of the recent metabolomics study which reported changes in amino acid signatures in SCZ affected individuals (He et al, 2012 ; Parksepp et al, 2020 ). In addition to this a study by Chen et al reported arginine and proline metabolism as one of the differential metabolic pathways in violent schizophrenia affected participants (Chen et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…We further performed a gene enrichment analysis using 227 DEGs compiled from microarray studies. Enrichment of arginine, proline metabolism pathway in our analysis is in agreement with the findings of the recent metabolomics study which reported changes in amino acid signatures in SCZ affected individuals (He et al, 2012 ; Parksepp et al, 2020 ). In addition to this a study by Chen et al reported arginine and proline metabolism as one of the differential metabolic pathways in violent schizophrenia affected participants (Chen et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have been performed to identify metabolites changes and biomarkers in schizophrenia (6,7). Abnormal biological levels have been reported in patients with schizophrenia for several metabolites, including N-acetyl aspartate, lactic acid, tryptophan, glutamic acid, phospholipids, kynurenine, and creatine (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the differential expression of creatinine reflected the perturbations of normal energy metabolism levels in schizophrenia patients, possibly leading to psychiatric symptoms [33] . Ornithine has been reported as a biomarker for SZs in serum or plasma [34] . The abnormal expression of ornithine in schizophrenia fits with decreased urea metabolism [35] .…”
Section: Resultsmentioning
confidence: 99%